Backmatter (Publication Ethics, Copyright Transfer Agreement for Publishing Form) - Istadi, Istadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Backmatter (Publication Ethics, Copyright Transfer Agreement for Publishing Form)